An essential guide to biopharmaceuticals - Aebisher, David (Biochemistry research trends series., 2020)
"This book provides a current review of the field of biopharmaceutical pharmacology. Biopharmaceuticals are drugs obtained in biotechnological processes using living organisms such as bacteria and fungi. An analysis was performed from biochemical and physiological point of view. This book covers an essential guide to current knowledge and analysis of biopharmaceuticals (Chapter 1-5). The composition of the biopharmaceuticals is provided. In this book we also discuss the historical point of view of the use of archeological botany, medicinal plants, strategies and main advances in communication between the nature and the advances of biopharmacy (Chapter 6-8). This book reports results from experimental and clinical work (Chapter 9). The book includes data regarding the therapy in combination with chemotherapeutic agents"--